AN INVESTIGATION OF ATTITUDES OF PRESERVICE TEACHERS TOWARDS USING TECHNOLOGY IN COURSES - PALA, Aynur (Atlas Journal, 2018)
This research study aimed to investigate the attitudes of preservice teachers’ towards using technology in courses. The importance of this topic was underlined in the comprehensive literature review that highlighted the existing debate between technology being a vital aid and helpful in colleges. The 276 student participated from Faculty of Education at The Manisa Celal Bayar University, were all enrolled teacher traning programmes and had access to technology. In the survey, there were two different sections of questions. The first section was about the demographic charactersitics of the participants. The second section consisted of twelve questions about how using technologies tools helped in classrooms. Participants responded on a 5-point Likert-type scale, from 1 (Strongly disagree) to 5 (Strongly agree) Likert Scale of 1–5, with 5 having the highest value was used in the survey. The study results provided conclusive evidence that students viewed the use of technology as an effective, helpful way of learning and improve the learning process in the classroom.